A Biomechanical Comparison of Isometric and Anatomic Medial Patellofemoral Ligament Reconstruction - Houdek, Christopher G.; Esquivel, Amanda O.; Cracchiolo, Allison M.; Lemos, Stephen E. (The Journal of Knee Surgery, 2016)
The purpose of this study was to compare two different methods of medial patellar femoral ligament (MPFL) reconstructions: isometric and anatomic. These were then compared with the native MPFL. Fourteen fresh frozen cadaveric knees were carefully dissected to expose the MPFL. The patella was laterally translated 10 mm using an Instron and values were recorded for the intact ligament and the reconstructions. Neither the anatomic nor the isometric reconstructions completely restored the biomechanical properties of the intact MPFL. There were fewer differences between the isometric reconstruction and the intact specimens. The higher forces and stiffer constructs that occurred with the anatomic reconstruction may suggest that this reconstruction technique could overconstrain the patellofemoral joint.
Keywords: medial patellofemoral ligament reconstruction; sports medicine; knee; biomechanics